2021
DOI: 10.2147/opth.s314288
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Antioxidant Supplementation in Patients with Glaucoma

Abstract: Purpose Oxidative stress may be a risk factor for glaucoma, and many previous reports have suggested that antioxidants could be a promising treatment. Here, we investigated the effects of a novel supplement containing three food-derived antioxidants (hesperidin, crocetin, and Tamarindus indica ) on markers of oxidative stress in patients with glaucoma. Patients and Methods This study had a prospective, single arm design. Thirty Japanese glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The treatment with LG saves a significant portion of these RGCs, and this is particularly relevant in peripheral retina, where LG treatment results in virtually complete rescue of the RGCs. According to these observations, both preclinical and clinical studies have reported RGC loss and PERG defects in glaucomatous retinas, which were protected by antioxidant treatments obtained with nutritional supplements ( Parisi et al, 2014 ; Cammalleri et al, 2020 ; Himori et al, 2021 ; Oddone et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…The treatment with LG saves a significant portion of these RGCs, and this is particularly relevant in peripheral retina, where LG treatment results in virtually complete rescue of the RGCs. According to these observations, both preclinical and clinical studies have reported RGC loss and PERG defects in glaucomatous retinas, which were protected by antioxidant treatments obtained with nutritional supplements ( Parisi et al, 2014 ; Cammalleri et al, 2020 ; Himori et al, 2021 ; Oddone et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“… 53 Recently, we performed a clinical study that revealed that an antioxidant supplement including hesperidin, crocetin, and Tamarindus indica improved antioxidant levels in the blood of glaucoma patients with high oxidative stress. 54 Therefore, dietary supplementation with plant containing hesperidin, crocetin, or Tamarindus indica has potential as a new therapeutic approach to protect against retinal damage associated with excitotoxic injury in diseases such as glaucoma and diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin is a flavanone commonly found in citrus fruits such as oranges, tangerines, lemons and grapefruits, known for its anti-inflammatory, antioxidant and anticarcinogenic properties [221]. The antioxidant profile of a novel supplement containing hesperidin, and two other food-derived antioxidants, i.e., crocetin and Tamarindus indica (tamarind), was assessed in a prospective, single-arm design trial involving 30 NTG patients receiving the supplements for 8 weeks [222]. In patients with relatively high oxidative stress, the supplement significantly reduced the urinary 8-hydroxy-2 -deoxyguanosine (8-OHdG; a marker of oxidative DNA damage) level, and the biological antioxidant potential was also significantly elevated [222].…”
Section: Hesperidinmentioning
confidence: 99%